Which energy citizenship in positive energy districts? A governmentality social psychological analysis of participatory governance - Nguyen, M. T.; Batel, S. (Journal of Environmental Policy and Planning, 2024)
Towards low carbon energy transitions, the EU is developing Positive Energy Districts (PEDs) which produce more renewable energy than they consume. This implies more participatory governance which decentralises and democratises energy decisions to citizens, as captured in the emergent concept of ‘energy citizenship’. However, it has been argued that these governmental strategies and the energy citizens they create have been co-opted by a neoliberal governmentality. This may limit citizens’ rights and responsibilities as only consumers/prosumers in the private sphere. However, the neoliberal form of energy citizenship as well as potential alternative forms have seldom been empirically examined, so the main aim of this paper is to analyse which representations of energy citizenship are fostered in PED policies at EU, national, and local levels in a case study of Torres Vedras, Portugal. The analysis, which combines a governmentality approach with the critical social psychology of citizenship, unveils neoliberal energy citizenship as the hegemonic representation in these policies, and identifies emancipated representations of energy citizenship based on entrepreneurial energy activism and energy localism.